Comparative Evaluation of LSTM and Metaheuristic-Optimized Neural Networks for ECG Prediction under Limited Data Conditions - Giovanni Dimas Prenata; Ahmad Ridho’i; Mohd Rizal Arshad (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2026)
This study presents a comparative evaluation of Deep Feedforward Neural Network (DFFNN) models optimized using single-stage metaheuristic approaches, including Genetic Algorithm (GA), Particle Swarm Optimization (PSO), and Grey Wolf Optimization (GWO), as well as a multi-stage hybrid optimization strategy (GA+GWO) for ECG-based emotion classification. The experimental dataset consists of ECG recordings collected from three elderly participants using a Sparkfun AD8232 sensor under controlled emotional stimuli, representing a limited-subject and small-data scenario. Feature extraction is conducted using Heart Rate Variability (HRV) parameters derived from both time domain (Mean RR, SDNN, RMSSD, Mean HR, and STD HR) and frequency domain (LF, HF, and LF/HF ratio). Experimental results from six repeated trials demonstrate that the multi-stage DFFNN+GA+GWO model achieves the best optimization performance, yielding the lowest Mean Squared Error (MSE) of 0.01599 and a consistent training accuracy of up to 85.71%. Compared with single-stage optimization methods, the hybrid approach exhibits improved convergence behavior and reduced performance variance, indicating enhanced optimization stability. However, test accuracy remains relatively limited (33.33%–50.00%), reflecting constrained generalization capability due to the small dataset and the absence of subject-wise or external validation. Further statistical analysis using confidence intervals and nonparametric testing confirms that the observed performance improvements are primarily associated with optimization stability rather than statistically significant gains in predictive generalization. Therefore, this study emphasizes the role of metaheuristic optimization in stabilizing neural network training under limited data conditions. The findings should be interpreted as a pilot feasibility study, and future work is required to validate the proposed approach using larger, more diverse datasets and more rigorous validation strategies.